2015
DOI: 10.1111/jocn.13083
|View full text |Cite|
|
Sign up to set email alerts
|

Factors associated with medication adherence in patients living with cirrhosis

Abstract: Study findings have the potential to change clinical practice especially the way nurses target motivational adherence counselling, key treatment messages, education and adherence monitoring. The results presented here provide a basis for developing adherence strategies and nursing management plans to improve adherence and health outcomes in people with cirrhosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
2
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 31 publications
(49 reference statements)
1
38
2
2
Order By: Relevance
“…Patients with cirrhosis including some with compensated cirrhosis are on multiple medications with an average between 3 and 10 medications . Volk et al showed that in patients with cirrhosis, the number of medications at discharge can predict time to readmission .…”
Section: Structural Barriers To Optimal Medication Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with cirrhosis including some with compensated cirrhosis are on multiple medications with an average between 3 and 10 medications . Volk et al showed that in patients with cirrhosis, the number of medications at discharge can predict time to readmission .…”
Section: Structural Barriers To Optimal Medication Managementmentioning
confidence: 99%
“…Higher scores were not associated with adherence. Thirdly, one in three patients stated they would adjust their medications if their symptoms improved without talking to their physicians …”
Section: Structural Barriers To Optimal Medication Managementmentioning
confidence: 99%
“…Illness and medication beliefs have been shown to influence patients’ confidence to self-manage alcoholic liver disease and to have impacts on health-related QoL [49]. Progression of disease is associated with decreased QoL, including increased symptoms; abdominal symptoms and fatigue have been found to worsen adherence in people with cirrhosis [50]. Investigation of the effect of these variables on medication adherence in patients with decompensated cirrhosis, in addition to the effect of a clinical pharmacist education and medication management intervention on modifying these variables, will provide valuable information for future ambulatory management of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, most medication adherence studies describe patient forgetfulness as the greatest barrier to non-adherence (30)(31)(32)(33). This is considered a non-intentional factor.…”
Section: Behavior-specific Cognitions and Affectmentioning
confidence: 99%